Republic of Lithuania : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Lithuania. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses key issues pertaining to the economy of Lithuania. Good policies and favorable business conditions have helped put Lithuania back on the convergence path with western European living standards. Last year, growth took a temporary hit from difficult external environment. External factors caused the price level to fall in 2015, but deflation is unlikely to take root. The external current account moved into moderate deficit in 2015 due to weak export markets and strong domestic demand. Lithuania needs to focus on raising productivity growth through structural reforms, securing continued competitiveness as labor market tightens, and reducing income inequality through fiscal measures while maintaining a prudent policy stance.